Galactorrhea During Duloxetine Treatment: A Case Report - Korkmaz, Sevda; Kuloglu, Murat; Isik, Umut; Saglam, Sadullah; Atmaca, Murad (Turkiye Sinir ve Ruh Sagligi Dernegi, 2011)
High prolactin hormone level in the blood is known as hyperprolactinemia. The most common symptom of hyperprolactinemia is galactorrhea, in which spontaneous milky discharge is seen from all ducts of the 2 mammary glands. Galactorrhea occurs due to different medical conditions, including the use of antidepressant medications. Herein we report a hyperprolactinemia case with galactorrhea due to duloxetine treatment for depression.
Keywords: Galactorrhea; duloxetine; prolactin